The Influence of Zinc Oxide Nano Particle on the Adhesion and Abrasion Properties of Graphene Oxide/Epoxy Composite System for Pipeline Application - RAHMAD, MUHAMMAD AIMAN HAKIM (2018)
With the advancement of technology nowadays, pipelines play major role in the industries across the globe. Essentially, pipelines are used for transporting and distributing chemicals, petroleum products and also food. Without pipelines, most of the infrastructure in the world will collapse thus it will give bad impact to the economy. However, it is not an easy task to maintain this vast infrastructure which usually it will lead to a corrosion problem. Corrosion in pipelines is a common issue in the industries and most of the time scientist and engineer try to solve with various method. Hence, one of the method to avoid this problem is the coating application either internal or external. By applying normal epoxy resins as the coating material can be facile way, but the major problems are epoxy is tend to be brittle and have low fracture toughness. With the help of Graphene Oxide (GO), it scientifically can increase the corrosion resistance performance in the epoxy system. Thus, in this project, different weight percentage of ZnO were used in order to enhance GO in the epoxy composites. Results shows that by adding ZnO as nanofiller, it can increase the abrasion properties of the epoxy matrix. As the ratio of ZnO being decorated into GO in the epoxy system, the wear index of the coating decrease. Lower wear index indicates higher fracture toughness in term of abrasion properties. Meanwhile for adhesion properties, only sample which the highest weight percentage of ZnO in the epoxy composite had the highest pull-off force and it indicates that adhesion quality can be increase as the amount of ZnO nanofiller increase. In other hand, sample with had less weight percentage of ZnO in the epoxy system had lower pull-off force which resulting poor adhesion quality. Hence, by adding ZnO as nanofiller into GO in the epoxy composites, it will give better performance in abrasion and adhesion properties.